1980
DOI: 10.1002/eji.1830100714
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and cytochemistry of human peripheral blood lymphocytes. Similarities between the cells of the third population and TGlymphocytes

Abstract: The ultrastructural and cytochemical features of human peripheral blood TG cells (T cells with receptors IgG) and of the cells of the so-called third population (non-T, non-B cells with high avidity receptors for IgG) have been investigated and compared. Both TG and third-population cells (TPC) contained acid hydrolases with a paranuclear localization of alpha-naphthyl acid esterase, beta-glucuronidase or acid phosphatase. At the electron microscopy level, TG and TPC were indistinguishable and displayed rough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(30 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…Typical small lymphocytes could be distinguished from other lymphocytic cells by their smaller size, relatively scantier cytoplasm, thicker peripheral rim of chromatin in the nucleus and the occasional presence of a deep indentation in the nuclear outline, which is corroborated, with the findings of Ferrarini et al (1980), in mammals and King & McLelland (1981) in birds. The reticular cells usually appeared larger than lymphocytes and had a more abundant and organized cytoplasm.…”
Section: Tonsillar Folliclessupporting
confidence: 61%
“…Typical small lymphocytes could be distinguished from other lymphocytic cells by their smaller size, relatively scantier cytoplasm, thicker peripheral rim of chromatin in the nucleus and the occasional presence of a deep indentation in the nuclear outline, which is corroborated, with the findings of Ferrarini et al (1980), in mammals and King & McLelland (1981) in birds. The reticular cells usually appeared larger than lymphocytes and had a more abundant and organized cytoplasm.…”
Section: Tonsillar Folliclessupporting
confidence: 61%
“…When CD3-crosslinked lymphocytes were treated with LTX, the ultrastructural features of untreated normal lymphocytes reappeared. Ferrarini et al 26 have described a subset of T lymphocytes in peripheral human blood, which display ultrastructural features identical to those of activated lymphocytes as seen in our study (Figure 1a). Details of the method of cell purification and functional properties of isolated cells, primarily the expression of high-affinity receptors to IgG (CD64 by the current classification), strongly suggest that the authors observed activated lymphocytes.…”
Section: Discussionsupporting
confidence: 86%
“…The cloned cells also resembled published descriptions of LGL isolated by a combination of gradient and rosetting techniques (31-36), with the exception that parallel tubular arrays were not seen. Although some authors have considered these structures to be characteristic of LGL (33, 34, 36), they have not been observed in all studies (31,32,35). When the human cloned NK cell JTB18 was cultured for 24 h in medium containing [35S]sulfate, radioactivity was incorporated into macromolecules in a linear fashion (Fig.…”
Section: Discussionmentioning
confidence: 99%